Partisans about memory and soviet heritage - Anušauskas, Arvydas (Genocidas ir rezistencija, 2000)
On 30 March 1949 the headquarters of the Lithuanian partisan Duke Margis’ Detachment (Algimantas District) issued an appeal “Lithuanians, let’s collect the material of the Bolshevik rule” and instructions on how to collect this material. Half a century later, the debate in Lithuania about the legacy of the Soviet period has brought back the sentiments of the Lithuanian resistance: “instead of destroying them, we should keep them, preserve them, so that they are not lost”. This was said not only about documents, but also about works of visual art (posters, etc.). Everything was to contribute to the common goal of not forgetting Lithuania and reminding the world not only of the crimes of the communist regime, but also of the spiritual oppression. No sphere of life was to be overlooked – not only the destruction of cultural heritage, but also the ‘bolshevisation’ of art. An interesting detail is that the instructions forbid any pre–selection of the material to be collected. All traces of communist rule were to be given equal weight, recognised as equally important.
Keywords: Soviet occupation; armed resistance; partisans